Poisson's Ratio and Auxetic Properties of Natural Rocks. Issue 2 (2nd February 2018) - Ji, Shaocheng; Li, Le; Motra, Hem Bahadur; Wuttke, Frank; Sun, Shengsi; Michibayashi, Katsuyoshi; Salisbury, Matthew H.
Abstract: Here we provide an appraisal of the Poisson's ratios ( υ ) for natural elements, common oxides, silicate minerals, and rocks with the purpose of searching for naturally auxetic materials. The Poisson's ratios of equivalently isotropic polycrystalline aggregates were calculated from dynamically measured elastic properties. Alpha‐cristobalite is currently the only known naturally occurring mineral that has exclusively negative υ values at 20–1, 500°C. Quartz and potentially berlinite (AlPO4 ) display auxetic behavior in the vicinity of their α ‐ β structure transition. None of the crystalline igneous and metamorphic rocks (e.g., amphibolite, gabbro, granite, peridotite, and schist) display auxetic behavior at pressures of >5 MPa and room temperature. Our experimental measurements showed that quartz‐rich sedimentary rocks (i.e., sandstone and siltstone) are most likely to be the only rocks with negative Poisson's ratios at low confining pressures (≤200 MPa) because their main constituent mineral, α ‐quartz, already has extremely low Poisson's ratio ( υ  = 0.08) and they contain microcracks, micropores, and secondary minerals. This finding may provide a new explanation for formation of dome‐and‐basin structures in quartz‐rich sedimentary rocks in response to a horizontal compressional stress in the upper crust. Plain Language Summary: Here we provide an appraisal of the Poisson's ratios ( υ ) for natural elements, common oxides, silicate minerals, and rocks with the purpose of searching for naturally auxetic materials. The Poisson's ratios of equivalently isotropic polycrystalline aggregates were calculated from dynamically measured elastic properties. Alpha‐cristobalite is currently the only known naturally occurring mineral that has exclusively negative υ values at 20–1, 500°C. Quartz and potentially berlinite (AlPO4 ) display auxetic behavior in the vicinity of their α ‐ β structure transition. None of the crystalline igneous and metamorphic rocks (e.g., amphibolite, gabbro, granite, peridotite, and schist) display auxetic behavior at pressures of >5 MPa and room temperature. Our experimental measurements showed that quartz‐rich sedimentary rocks (i.e., sandstone and siltstone) are most likely to be the only rocks with negative Poisson's ratios at low confining pressures (≤200 MPa) because their main constituent mineral, α ‐quartz, already has extremely low Poisson's ratio ( υ  = 0.08) and they contain microcracks, micropores, and secondary minerals. This finding may provide a new explanation for formation of dome‐and‐basin structures in quartz‐rich sedimentary rocks in response to a horizontal compressional stress in the upper crust. Key Points: A comprehensive review of Poisson's ratios for natural elements, common oxides, silicate minerals, and rocks is provided Quartz‐rich sedimentary rocks are most likely the only natural rocks with negative Poisson's ratios at low‐pressure conditions A new interpretation is proposed for formation of dome‐and‐basin structures in quartz‐rich rocks in terms of auxetic mechanics